FAKTOR-FAKTOR YANG MEMPENGARUHI PENGIRIMAN REMITAN MIGRAN NON PERMANEN DI DESA ADAT KEDONGANAN – BALI - Reshmasari, Ni Putu Yuki; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
This study aims to analyze effect of income, number of family members covered in the area of origin, length of employment, marital status simultaneously and partially on non-permanent migrants' remittances in Kedonganan Traditional Village, and analyze the differences in remittances between non-permanent migrants who are married and unmarried. Data collection through structured and in-depth interviews. A sample of 148 people was taken through purposive sampling. The data analysis technique used multiple linear regression. Based on results, simultaneously income, number of family members covered in the area of origin, length of employment, marital status have significant effect on non-permanent migrant remittances. Partially income and number of family members covered in area of origin have positive and significant effect, length of employment has no significant effect on remittances for non-permanent migrants. Remittances for married migrants are no different from those of non-permanent migrants with unmarried status. keyword : remittances, income, number of family members covered in the area of origin, length of employment, marital status